A cestaria Ooloda/Urutú: patrimônio material do povo Medzeniako do município de São Gabriel da Cacheiroa-Amazonas-Brasil - Garrido, Ronaldo Jose (2024)
This research aimed to contribute to the strengthening and preservation of Cultural Memory, Ooloda/Urutú basketry, its production, meaning and appreciation of the cultural and material heritage of the Medzeniako people. The account of the history and relevance of Ooloda/Urutú basketry for the Medzeniako people; describing in the Medzeniako language and Portuguese the designs of Ooloda/Urutú basketry and reporting the meaning of the material makes the work a reference for the strengthening, practice, production and appreciation of Ooloda/Urutú Medzeniako. The relevance is also justified by seeking to record the technique, meaning and ancestral use of Ooloda/Urutú basketry among the Medzeniako. Medzeniako is the indigenous people who live in the Içana River basin, Indigenous Land of the upper Rio Negro. Knowledge reporting is relevant because it is a strategy for valuing and strengthening culture. Thus, the research focuses precisely on being a means of strengthening and cultural (re)existence of the Medzeniako people through the “production of Ooloda/Urutú basketry”. The research took place through dialogue and recording information with Ooloda/Urutú basketry producers. Together, it was possible to carry out and define the meaning of the reported experiences and identify aspects related to oral and cultural memory in relation to the Ooloda/Urutú basketry production technique, its relevance, cultural and heritage significance for the Medzeniako.